Pengaruh Kriteria Teknis Dana Alokasi Khusus (DAK) Bidang Jalan Terhadap Jaringan Jalan pada Beberapa Pulau di Indonesia - Meriana, Desi; Subagio, Bambang Sugeng; Najid, Najid (Jurnal Teknik Sipil, 2024)
Abstract The study aims to analyze the influence of technical data criteria variables and determine the best model criteria. The criteria analyzed included pavement deterioration, bridge condition, road performance, local budget allocation for road capital expenditure, allocation of local budget government for routine maintenance of roads, e-monitoring reporting, and shp map reporting. This evaluation is needed to highlight the importance of comprehensive data testing to provide an overview of the road infrastructure data used as the basis for Special Allocation Fund (DAK) allocations, considering the different characteristics between islands in Indonesia. The methods used include Multiple Linear Regression with dummy variables and Binary Logistic Regression. The study's results show that Nusa Tenggara and Bali Islands have the best model for explaining the variation of kjtm and npe variables, with better consistency and significance, while Java Island shows a significant influence of Kj, Kij, and Aprj variables on road quality. Keyword: Technical data ctriteria, technical criteria, DAK, regression, road quality